Analysis of Consumer Intention to Resist Electric Motorcycles Product Purchase : an Innovation Resistance Theory Approach - Damayanti, Nenty; Nurmahdi, Adi (Journal of Sustainable Economic and Business, 2026)
Objectives: Electric motorcycles have been promoted as a sustainable transportation solution; however, consumer adoption in Indonesia remains relatively limited, indicating the existence of resistance toward this innovation. This study aims to analyze the factors influencing consumers’ intention to resist electric motorcycle product purchase using the Innovation Resistance Theory (IRT) approach.Methodology: This research adopts a quantitative research approach using a survey method. Data were collected through an online questionnaire from 221 respondents selected using purposive sampling, consisting of individuals aged 18–56 years who reside or work in Jabodetabek and Yogyakarta and are familiar with electric motorcycles. The collected data were analyzed using PLS-SEM with SmartPLS 4.1.1.4 software to examine the relationships among the innovation resistance variables.Finding: The results reveal that usage barrier, value barrier, tradition barrier, and image barrier have a positive and significant effect on consumers’ intention to resist electric motorcycle product purchase, while risk barrier does not show a significant effect. Among all barriers, tradition barrier is identified as the most dominant factor contributing to consumer resistance.Conclusion: Consumer resistance toward electric motorcycle product purchase in Indonesia is mainly driven by behavioral, value-related, and perceptual barriers rather than perceived risk. The dominance of tradition barrier highlights the strong influence of habitual reliance on conventional motorcycles, indicating that efforts to accelerate adoption should prioritize behavior change strategies, value enhancement, and image improvement rather than focusing solely on technical aspects.